Understanding nanoparticle porosity via nanoimpacts and XPS: electro-oxidation of platinum nanoparticle aggregates - Jiao, X; Tanner, E; Sokolov, S; Palgrave, R; Young, N; Compton, R (Royal Society of Chemistry, 2017)
The porosity of platinum nanoparticle aggregates (PtNPs) is investigated electrochemically via particle-electrode impacts and by XPS. The mean charge per oxidative transient is measured from nanoimpacts; XPS shows the formation of PtO and PtO2 in relative amounts defined by the electrode potential and an average oxidation state is deduced as a function of potential. The number of platinum atoms oxidised per PtNP is calculated and compared with two models: solid and porous spheres, within which there are two cases: full and surface oxidation. This allows insight into extent to which the internal surface of the aggregate is ‘seen’ by the solution and is electrochemically active.